Intestinal Perforation in the Context of Thoracoamniotic Shunting and Congenital Diaphragmatic Hernia - Dassios, Theodore; Hassan, Wassim A.; Kazmierski, Marcin; Carroll, Daniel; Ahluwalia, Jag (European Journal of Pediatric Surgery Reports, 2013)
A fetus was diagnosed by prenatal ultrasound with bilateral intrauterine pleural effusions that were subsequently drained in utero by insertion of bilateral thoracoamniotic shunts. Serial prenatal ultrasound scans were consistent with a left-sided diaphragmatic hernia. On the first day of life, the infant underwent an exploratory laparotomy for intestinal obstruction, with radiographic findings of pneumatosis intestinalis. Intraoperative findings were suggestive of prenatal bowel and diaphragm perforation, which might have occurred as a complication of thoracoamniotic shunting.
Keywords: intestinal perforation; thoracoamniotic shunt; diaphragmatic hernia